An ethnobotanical study on the medicinal herb practices of the gelao ethnic minority in North Guizhou, China: an exploration of traditional knowledge - Liu, Fusong; Peng, Jie; Feng, Yi; Ma, Yuhan; Ren, Yan; Sun, Pei; Zhao, Yongxia; Liu, Sha; Wu, Faming; Xie, Jian (Frontiers in Pharmacology, 2023)
The Gelao ethnic minority of northern Guizhou, China have long possessed extensive traditional knowledge of medicinal herbs. This ethnobotanical study aimed to document and evaluate wild plants used medicinally by the Gelao people, providing insights into their traditional medicine and knowledge systems. Field research was conducted in Gelao communities of Daozhen, Wuchuan and Zheng'an counties using interviews, surveys and participatory rural appraisal. Quantitative ethnobotanical indices were utilized to assess the cultural significance of 187 herbs identified. The herbs belonged to 84 families, primarily Compositae, and were mostly roots, rhizomes and whole plants. They were used to treat digestive, respiratory and inflammatory disorders, gynecological diseases, bites and other conditions, mainly through decoctions. 25 highly significant herbs (national plant cultural significance index > 1000) were known to protect health. Some function as food and are considered safe. However, the study revealed issues including a declining number of knowledgeable elders and inadequate hygiene controls. Our findings demonstrate the Gelao's extensive medicinal plant knowledge and highlight the need for further ethnobotanical research to document and preserve this culturally important tradition. The identified herbs also represent an alternative medicinal resource with potential modern applications pending further investigation of their pharmacology and sustainable use. Overall, this study provides valuable insights into Gelao ethnobotanical knowledge and the potential of indigenous medicine for modern healthcare.